Crucial biological functions of CCL7 in cancer - Liu, Yangyang; Cai, Yadi; Liu, Li; Wu, Yudong; Xiong, Xiangyang (PeerJ, 2018)
Chemokine (C-C motif) ligand 7 (CCL7), a CC chemokine, is a chemotactic factor and attractant for various kinds of leukocytes, including monocytes and neutrophils. CCL7 is widely expressed in multiple cell types and can participate in anti-inflammatory responses through binding to its receptors to mediate the recruitment of immune cells. Abnormal CCL7 expression is associated with certain immune diseases. Furthermore, CCL7 plays a pivotal role in tumorigenesis. CCL7 promotes tumor progression by supporting the formation of the tumor microenvironment and facilitating tumor invasion and metastasis, although some studies have suggested that CCL7 has tumor suppressor effects. In this review, we summarize the currently available information regarding the influence of CCL7 on tumors.
Keywords: CCL7; Chemokines; Physiological function; Tumor microenvironment; Tumorigenesis